A Rainwater Harvesting and Treatment System for Domestic Use and Human Consumption in Native Communities in Amazonas (NW Peru): Technical and Economic Validation. (19th October 2021) - Morales Rojas, Eli; Díaz Ortiz, Edwin Adolfo; Medina Tafur, Cesar Augusto; García, Ligia; Oliva, Manuel; Rojas Briceño, Nilton B.
Abstract : The inhabitants of Tunants and Yahuahua face water supply problems in terms of quantity and quality, leading to socio-environmental and health impacts in the areas. The objective of this research, therefore, is to determine the technical and economic feasibility of a proposal for a rainwater harvesting and treatment system for human consumption in the native communities. For the technical feasibility, monthly water demand per family was compared with the amount of water collected in the rainy and dry seasons. In addition, 16 physical, chemical, and microbiological parameters were evaluated at the inlet and outlet of the water system. The economic feasibility was determined by the initial investment and maintenance of the systems; with the benefits, we obtained the net present social value (NPSV), social internal rate of return (SIRR), and cost-effectiveness (CE). Technically, oxygenation and chlorination in the storage tanks allowed for water quality in physical, chemical, and microbiological aspects, according to the D.S. N° 031-2010-SA standard, in all cases. Finally, with an initial investment of S/2, 600 and S/70.00 for annual maintenance of the system, it is possible to supply up to six people per family with an average daily consumption of 32.5 L per person. It is suggested that the system be used at scale in the context of native communities in north-eastern Peru.